Implementasi Pelaporan Keuangan Pada Panti Asuhan Beabdurrohim - Rifdah Auliyah Murat; Maulidah Narastri (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
BeAbdurrohim Gresik Orphanage Dusun Bunut, Randegansari, Kec. Driyorejo, Gresik Regency, East Java. The orphanage is a non-profit organization, where the orphanage management has full responsibility in matters of trust. which has been given in terms of running the operations of the orphanage. As a form of public sector non-profit organization, one of the sources of funding for orphanages is in the form of donations from regular donors or incidental donors. This research aims to identify the implementation of the Financial Reports of the BeAdburrahim orphanage when viewed from ISAK 35 regarding non-profit organizations. The research was carried out using primary data, namely interviews and field observations, as well as secondary data in the form of financial reports at orphanages. The type of research that will be used is using a descriptive qualitative method by describing the state of the research object and then comparing it with existing standards.